A Profile of Heart Failure with Preserved Ejection Fraction in a Teaching Hospital (Bangladesh Journal of Medical Science, 2021)
Objective: Heart failure with preserved ejection fraction (HFPEF) is fast becoming animportant public health issue. Nearly fifty percent of all heart failure cases are due to HFPEF.There are many associated comorbidities has been associated with this condition which maybe pathophysiologically related. There is no specific treatment yet. The focus remains onsymptomatic treatment of heart failure along with carefully managing the associated conditions.The present study was aimed at analyzing the comorbidities in HFPEF in a tertiary care centre.Method: Patient diagnosed with heart failure wereechocardiographically analyzed. Thoseshowing diastolic dysfunction on tissue Doppler imaging were diagnosed as HFPEF. Patientswith chronic obstructive pulmonary disease, valvular heart disease, constrictive pericarditis,restrictive/ hypertrophic cardiomyopathy and sepsis related diastolic dysfunction were excluded.One hundred such patients fulfilling the inclusion and exclusion criteria were enrolled. Plasma Btype natriuretic peptide(BNP) level was assayed in all participants. Institutional Ethics Committeeapproval was taken beforehand. Written informed consent was taken from each patient.Result: The mean age of the patients in the study group was 63.06yrs. HFPEF was more commonin females(62%). The common comorbidities observed were hypertension(82%), high bodymass index (80%),anaemia (76%), hyperlipidemia (30%) diabetes mellitus(28%). The plasmaBNP was elevated in all except 2 patients. The BNP level was higher in those with higherleft atrial size and those showing more severe diastolic dysfunction on tissue doppler imaging.Conclusion- HFPEF can be diagnosed clinically with the help of echocardiography. Plasma BNPlevel assay may be done when diagnosis is in doubt. The patients with HfpEf are heterogeneousand treatment need to be individualized depending on the associated comorbidities. Furtherstudies with larger sample size are required to define the profile of this disease.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.39-44